Impact of compaction process on the carbon epoxy composite under varied environmental conditions - Maryam Al Kuwaiti; Amir Hussain Idrisi; Asima Zahoor; Mostafa S. A. ElSayed; Dinu Thomas Thekkuden; Abdel-Hamid I. Mourad (Scientific Reports)
Abstract Fibre-reinforced polymeric composites utilized in aerospace settings, experience varying environmental conditions throughout their operational lifespan. The major factors that can have adverse effects on their long-term performance are water and temperature. The present study investigates how the determinants such as water and temperature impact the structural integrity of plain weave woven carbon/epoxy laminated composites and further categorizing them into compacted and non-compacted groups. The compacted group involves in-process compactions during composite lay-up and the use of bleeders/breathers around the laminate, whereas the non-compacted group lacks these procedures. Specimens comprising twelve plies are created and submerged in water heating chambers set to different submersion temperatures (40 °C, 70 °C, and 95 °C) for durations ranging from 1 to 10 months. Through experimental analysis, mechanical, physical, and thermal characteristics are examined. The study analyses how temperature, moisture, and submersion duration contribute to the composite material’s degradation and compares the outcomes between the compacted and non-compacted groups. The findings indicate that both moisture and temperature negatively affect composite performance. Notably, specimens subjected to 90 °C submersion experience 6% reduction in tensile strength for the compacted group and a 14.8% reduction for the non-compacted group. While minimal disparities in thermomechanical properties are evident between the two groups at 40 °C and 70 °C submersion temperatures, a slight decline is noticeable at 95 °C. This suggests that for high-temperature applications, in-process compaction and the use of bleeders/breathers may be necessary for twelve-ply monolithic laminates.